99 Setting up a complex clinical trial. (22nd November 2019) - Shah, Sahra; Rosie-Wilkinson, Olivia; Jackson, Christopher
Abstract : Research Coordinators in the NIHR Clinical Research Facility (CRF) are often heavily involved in the set-up of clinical trials. The NIHR CRF's remit is early phase studies for rare diseases, with this comes complex research studies for children with complex needs. Setting-up complex trials has always been an exciting and demanding task which determines the smooth running of the study. The Senior Research Coordinators have put in place various tools to assist with set-up and provide support for potential issues which could arise. To help with the costing of procedures, interventions and staff time, guidelines have been created, highlighting the procedures specific to the CRF as well as common costs. Clinical Research is strictly governed by laws and guidelines, requiring approvals from multiple relevant regulatory authorities. These approvals ensure patient safety, confidentiality and well-being is respected. A study set-up tool has been created to track all external and internal approvals to assist with this. A complex trial often involves different specialities and procedures to schedule. We have to communicate effectively with the relevant support departments, to ensure adequate training has been provided and patient can be accommodated safely, with both the requirements of study protocol and patients fulfilled. To harmonize the process of contacting external departments, a template has been put in place providing us the assurance that each department is aware and ready to participate in the delivery of the trial. A coordinator study assessment tool has been implemented, taking into consideration the intensity and complexity of individual studies to make certain that staff resources are utilised effectively. With these tools in place, study set-up process has been facilitated and is running more effectively than ever within the CRF. Working across different departments as part of a large team of experts working collaboratively always make us feel proud.